Works by Contemporary British Artists from the Logan Collection : Now It's My Turn to Scream. - Bevan, Roger; Logan, Kent; Haines Gallery, San Francisco (San Francisco : San Francisco Museum of Modern Art, 1999)
Collishaw, Mat ; Emin, Tracey ; Gilbert & George ; Harvey, Marcus ; Hirst, Damien ; Hoberman, Nicky ; Hume, Gary ; Opie, Julian ; Patterson, Richard ; Patterson, Simon ; Quinn, Marc ; Stewart, Kerry ; Taylor-Wood, Sam ; Turk, Gavin ; Whiteread, Rachel
biografie
Now It's My Turn to Scream: Works by Contemporary British Artists from the Logan Collection, on view at Haines Gallery, San Francisco, from September 9 to October 9, 1999
Engels
boek
Keywords: Groot-Brittannië